Kombinasi algoritma base64 dan caesar cipher pada aplikasi - Devianto, Yudo; Gunawan, Wawan; Sukowo, Bambang; Susafaati, Susafaati (Faktor Exacta, 2024)
Digital information systems must also pay attention to data security because it is confidential, there are many problems with data security which result in loss of data or damage caused by irresponsible parties. This research will combine the BASE64 and CAESAR CIPHER algorithms in applications to maintain the security of financial data so that it cannot be seen by users who do not have access to the application. The system development in this research looks like in Figure 1 which uses the Extreme Programming method. The testing carried out was using Black box and white box testing which produced the same cyclomatic complexity value, namely 4. So it can be concluded that the system is running well because the testing produces the same value